Menyama Braya dalam Upanisad - Komang Fatmawati (Jurnal Pendidikan Agama, 2021)
This paper aims to convey an understanding of Brama Brama in the view of Upanishad. Upanisad is a book that cannot be separated from the Vedic scriptures. Even each part of the Chess Weda Samhita each has an Upanishad, albeit with different amounts. There are so many teachings contained in the Upanishads, one of which is the teachings on norms that teach about harmonization of life both human and human, human beings with God, and humans with the natural surroundings. Humans other than as individual beings are also at the same time as social beings where humans need interaction with other humans in order to meet their needs. Tri Hita Karana which in its division is Pawongan which means a harmonious relationship between humans and humans. The interactions that occur in Balinese Hindus are not only the application of the teachings of Tri Hita Karana but also as the application of the teachings of Tat Tvam Asi.